Diseño de recursos didácticos para niños y niñas del primer grado de la escuela de Educación Especial Azucena Chiang de Orellana del cantón Quevedo - Gomez Pianda, Javier Andrés (2017)
The research "design of didactic resources for children in the first grade of the special Education school Azucena Chiang de Orellana del Cantòn Quevedo" aims to help students to engage in a more direct and dynamic way in their educational process, Being thus able to have confidence and learning in a better way the most basic of the first degree, in order to continue advancing in the same conditions and level of quality as that of the other students, it is expected then that this investigation is one of the best Tools for first grade students. Promoting a better applied education for first graders in the Special School Azucena Chiang de Orellana, formerly known as the Municipal patronage of the child of Quevedo "Pamuniq". Given the field research carried out, with the application of the didactic material it was found that, if it is feasible and true that by eye-catching designs and new resources, students learn more and are interested in learning much more.